EVALUATION OF FIVE FLAGSHIP PROGRAMS OF BAZNAS USING INSTAGRAM SENTIMENT ANALYSIS - Nurfala Safitri (I-Finance Journal, 2024)
This study aims to analyze the effectiveness of promotional activities for the flagship programs of the National Amil Zakat Agency (BAZNAS) through Instagram and to evaluate the challenges encountered, such as promotional imbalance and low public trust due to a lack of transparency and consistency in communication. A quantitative text-based approach was employed, utilizing a sample of 135 captions from the BAZNAS Instagram account (@baznasindonesia) collected through web scraping. The analysis techniques included text mining, topic analysis, and promotional effectiveness evaluation based on keyword distribution. The findings revealed a promotional imbalance, with the "Indonesia Peduli" program dominating over others, such as "Indonesia Takwa" and "Indonesia Sehat." Additionally, analysis of BAZNAS’s fundraising reports indicated significant disparities in fund allocation, with the majority concentrated on the "Indonesia Peduli" program. The study concludes that BAZNAS's social media promotions need improvement to ensure a more balanced representation and effective zakat fundraising by enhancing transparency and consistency in communication to restore public trust.